2014
DOI: 10.1371/journal.pone.0085602
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Increases Reproductive Failure in Magellanic Penguins

Abstract: Climate change is causing more frequent and intense storms, and climate models predict this trend will continue, potentially affecting wildlife populations. Since 1960 the number of days with >20 mm of rain increased near Punta Tombo, Argentina. Between 1983 and 2010 we followed 3496 known-age Magellanic penguin (Spheniscus magellanicus) chicks at Punta Tombo to determine how weather impacted their survival. In two years, rain was the most common cause of death killing 50% and 43% of chicks. In 26 years starva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 73 publications
(117 reference statements)
2
89
0
2
Order By: Relevance
“…Although precipitation was not a key predictor variable in our models, it can cause the plumage of chicks to become damp or wet and is generally a major factor causing egg and chick mortality and slow growth due to hypothermia (Konarzewski & Taylor 1989, Thyen & Becker 2006. For example, Boersma & Rebstock (2014) found more chicks died when rainfall was high and air temperature was low. Wetness decreases the insulating properties of feathers, and this disruption likely increases heat loss (McCafferty et al 1997, Wilson et al 2004).…”
Section: Local Weather Predictors Of Cfmmentioning
confidence: 94%
“…Although precipitation was not a key predictor variable in our models, it can cause the plumage of chicks to become damp or wet and is generally a major factor causing egg and chick mortality and slow growth due to hypothermia (Konarzewski & Taylor 1989, Thyen & Becker 2006. For example, Boersma & Rebstock (2014) found more chicks died when rainfall was high and air temperature was low. Wetness decreases the insulating properties of feathers, and this disruption likely increases heat loss (McCafferty et al 1997, Wilson et al 2004).…”
Section: Local Weather Predictors Of Cfmmentioning
confidence: 94%
“…We used the proportion of chicks that starved as a proxy for food availability and foraging success (Boersma and Stokes 1995). Data on both the number of chicks starved in each year and the total number of chicks came from Boersma and Rebstock (2014), who showed that~40% of chick deaths each year are due to starvation.…”
Section: Selection Analysismentioning
confidence: 99%
“…Using data from 1983 to 2010, [78] determined that starvation and predation were the most important predictors of chick mortality across years in Magellanic penguins, although climate variability also negatively influenced reproductive success. The number of storms in early December, when all chicks are less than 30 days of age, increased during the period of this study.…”
Section: Population and Evolutionary Ecologymentioning
confidence: 99%